answersLogoWhite

0

How do you simplify x-8 8-x?

Updated: 10/17/2024
User Avatar

Wiki User

11y ago

Best Answer

8 times 8 = 64

User Avatar

Wiki User

14y ago
This answer is:
User Avatar
More answers
User Avatar

Wiki User

15y ago

84

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: How do you simplify x-8 8-x?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is x8 plus x9?

Do you mean what is 8x + 9x (=17x) ?


Simplify 8x 19x - 6y - -y?

27x - 5y


What is the answer to -27 8x - 5x?

Set up the equation and solve: -27 = 8x - 5x (next simplify by subtracting 5x from 8x)) -27 = 3x (next divide both sides of the equation by 3) -27/3 = 3x/3 (next simplify and solve) -9 = x


What is the answer to -27 equals 8x-5x show steps?

Set up the equation and solve: -27 = 8x - 5x (next simplify by subtracting 5x from 8x)) -27 = 3x (next divide both sides of the equation by 3) -27/3 = 3x/3 (next simplify and solve) -9 = x


What is the answer to 27 equals 8x 5x show steps?

Set up the equation and solve: -27 = 8x - 5x (next simplify by subtracting 5x from 8x)) -27 = 3x (next divide both sides of the equation by 3) -27/3 = 3x/3 (next simplify and solve) -9 = x


How do you work out negative 7 plus 8x plus forty plus ninety?

Since there is only an expression - not an equation - you can simplify it but there is nothing to work out or solve. -7 + 8x + 40 + 90 = 8x + 123


How do you simplify 8x - 8 - 4x - 3 3x?

To simplify the expression 8x - 8 - 4x - 3 - 3x, first combine like terms. Start by combining the x terms: 8x - 4x - 3x = x. Then, combine the constant terms: -8 - 3 = -11. Therefore, the simplified expression is x - 11.


How do you simplify 6x plus 9 plus 2x?

6x + 9 + 2x = 8x + 9


How do you simplify 4x plus 5x?

In this case you just add them together to make 9x.


How do you simplify this expression -8x plus 7y-x-6y plus 4x?

y-5x


What does evaluate meen in math?

In math evaluating is where you simplify an expression as much as possible. For example to evaluate 5+2 you simplify it so it is 7. To evaluate 5x+3x+4y you simplify it to 8x+4y.


Solve the equation for x 16x - 8x plus 12 equals 78 plus 22?

16x - 8x + 12 = 78 + 22 or simplified to (16x-8x=8x)(78+22=100) 8x + 12 = 100 Simplify some more (Subtract 12 from both sides) 8x = 88 Divide both sides by 8, and x = 11